Neural substrates for voluntary suppression of negative affect: A functional magnetic resonance imaging study - Phan, K. Luan; Fitzgerald, Daniel A.; Nathan, Pradeep J.; Moore, Gregory J.; Uhde, Thomas W.; Tancer, Manuel E. (Biological psychiatry (1969), 2005)
Successful control of affect partly depends on the capacity to modulate negative emotional responses through the use of cognitive strategies. Although the capacity to regulate emotions is critical to mental well-being, its neural substrates remain unclear. We used functional magnetic resonance imaging to ascertain brain regions involved in the voluntary regulation of emotion and whether dynamic changes in negative emotional experience can modulate their activation. Fourteen healthy subjects were scanned while they either maintained the negative affect evoked by highly arousing and aversive pictures (e.g., experience naturally) or suppressed their affect using cognitive reappraisal. In addition to a condition-based analysis, online subjective ratings of intensity of negative affect were used as covariates of brain activity. Inhibition of negative affect was associated with activation of dorsal anterior cingulate, dorsal medial prefrontal, and lateral prefrontal cortices, and attenuation of brain activity within limbic regions (e.g., nucleus accumbens/extended amygdala). Furthermore, activity within dorsal anterior cingulate was inversely related to intensity of negative affect, whereas activation of the amygdala was positively covaried with increasing negative affect. These findings highlight a functional dissociation of corticolimbic brain responses, involving enhanced activation of prefrontal cortex and attenuation of limbic areas, during volitional suppression of negative emotion.